Youth Rationality in the Digital Economy: Work Flexibility and Digital Skills of Jember University Students in Thrift and Skincare Businesses Through Social Media Platforms - Ama Putri, Manie Sari; Cantika S, Diajeng Anugrah; Putratama, Dava; Vicho V, Tegar (JUPE : Jurnal Pendidikan Mandala, 2025)
This study examines the rationality of youth in responding to the development of the digital economy, particularly in the context of work flexibility and digital skills acquisition. Amid rapid digital transformation, young people are required to make rational decisions in choosing career paths, developing skills, and utilizing digital platforms to create job opportunities that align with their lifestyles and personal needs. Using a qualitative approach through ethnographic methods, this research explores how youth actively engage with technology—such as social media and digital marketing—in their daily work practices, including flexible job models like freelancing and the gig economy. The study employs Max Weber’s theory of social action, particularly the concept of instrumental rational action, to understand how young people determine goals and select the means used in their digital economic activities. The findings reveal that youth leverage work flexibility and digital skills as strategies to achieve economic independence and build professional identities, while also facing dilemmas such as the trend of flexing, which emphasizes appearance over substance. This research concludes that the rationality of youth in the digital economy reflects a complex adaptation involving pragmatic values, personal needs, and social pressures in the digital era. The findings are expected to serve as a reference for policymakers in designing youth empowerment programs that are more responsive to the challenges and dynamics of the digital labor landscape.